Community-based Process Results in Strong Watchdog Committee for English Health and Social Services - Quebec Community Groups Network (QCGN) (2018)

Resources for Families with Special Needs - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Long Awaited Regulation Creating Provincial Access to Committee a First Step in the Right Direction - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Improving Access to Health and Social Services and Information in the English Language - Prata, Ghislaine (2018)

Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Adaption Gaspésie-Les-Îles 2014-2018 : Improved Access to Inter-Regional Health and Social Services for the English-speaking Population of Gaspésie-Îles-de-la-Madeleine - Community Health and Social Services Network (CHSSN) (2018)

Annual Report 2017-2018 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Investment Priorities 2013-2018 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Québec Health 101 Guide - Jeffery Hale Community Services; Community Wellness Centre; Voice of English-speaking Quebec (VEQ) (2018)
This guide and the accompanying presentation were developed with the intention of helping newcomers navigate the medical system here in Québec City with a little more ease and efficiency. This project was a joint effort between Jeffery Hale Community Services, the Community Wellness Centre and the Voice of English-speaking Québec. This document was inspired by the Valcartier Family Centre Health Guide.

Regional Priorities : QCGN Members 2018 - Quebec Community Groups Network (QCGN) (2018)
This document is a collaborative effort on the part of the regional member organization's of Quebec Community Groups Network to ensure regional priorities are at the fore of the Priority Setting Steering Committee discussions and to establish preferred and inclusive methods of consultation among regional member groups.

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2018 - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Programme de maintien en poste : Monitoring des stagiaires - Storr, Caroline; Hendrickson, Mary (2018)

Retention Program : Monitoring of Internship Students - Storr, Caroline; Hendrickson, Mary (2018)